Ifosfamide dose‐intensification for patients with metastatic Ewing sarcoma. Issue 4 (28th January 2015) - Magnan, Heather; Goodbody, Christine M.; Riedel, Elyn; Pratilas, Christine A.; Wexler, Leonard H.; Chou, Alexander J.
<x xml:space="preserve">Abstract</x> Background Outcomes for patients with metastatic Ewing sarcoma (ES) remain poor. We investigated whether the intensification of ifosfamide improved survival for patients with metastatic ES. Procedure We conducted a retrospective chart review of 30 patients with metastatic ES treated with the MSKCC "EFT regimen." The regimen included an intensification of ifosfamide dosing from 1, 800 mg/m2/day × 5 days per cycle to 2, 800 mg/m2/day × 5 days per cycle. Results Twenty six of the 30 patients completed planned chemotherapy. Two patients experienced disease progression during therapy. There were no toxic deaths. One patient developed secondary leukemia. The 4‐year event free survival (EFS) was 27% and the overall survival (OS) was 39%. Conclusions Intensification of ifosfamide was tolerated and did not increase toxicity in patients with metastatic ES. The intensification did not improve outcomes for these patients with metastatic disease. Pediatr Blood Cancer 2015;62:594–597. © 2015 Wiley Periodicals, Inc.